The effects of chilling and freezing to the crude fat, Ash and moisture content of Channa striata and Clarias batrachus / Sharir Aizat Kamaruddin ... [et al.] - Kamaruddin, Sharir Aizat; Jaafar, Muhammad Huzaifah; Zakariya, Muhammad Ariff; Fadzilan, Muhammad Fayyadh; Ahmad Nadzri, Aliff Iqbal; Abd.Aziz, Khairul Naim; Roslani, Muhammad Akmal; Zainol, Zamzila Erdawati (Universiti Teknologi MARA, Negeri Sembilan, 2020)
This research is conducted to investigate the effects of cubed and crushed ice on the crude fat, ash, and moisture content of Channa striata and Clarias batrachus. The samples were chilled to four and seven days in the Polyvinyl chloride plastic (PVC) boxes filled with cubed ice and crushed ice. Before the determination of crude, ash, and moisture content, the samples were frozen for 1 week. Statistical analyses were carried out to indicate the significant difference in the effects of treatment days and physical characteristics of ice towards the crude fat, ash, and moisture content. The result concludes that crushed ice is more superior to cubed ice for all experiments. The outcomes of this research benefit many parties specially to cubed ice suppliers to support aquaculture industries and the socio-economic sectors in Malaysia.